Convergencia educativa y diversidad cultural de EEES. Desde las aulas universitarias multiculturales de segundas lenguas (E/LE) hacia la competencia intercultural - Méndez Cea, Cecilia (Miscelánea Comillas, 2012)
In the frame of European university convergence towards the European Higher Education Area (EHEA), whose implementation means unifying educational criteria, approaches, methodologies, programmes, credit systems and degrees in the forty-seven participant countries, giving at the same time a positive appreciation to the cultural diversity involved and to its adequate treatment asessential factors for quality, it seems to be most relevant to analyze in detail, from the deeply multicultural Second Languages classrooms (SP/FL), the great cultural diversity present both in societies and university classrooms in Europe, in order to investigate in depth about universal criteria for educational quality in Higher Education as well as about those which are specific and diverse for beingas sociated to the cultural profiles of each member country, by analyzing the validity of preconceptions, values, attitudes, instructional and learning styles, expectations on educational quality, associated both to traditional university models in Europe (Humboldt/ Germanic Model, Napoleonic/ French Model, British/Anglo-Saxon Model, Soviet/ Eastern Europe Model) and to the cultural andacademic profiles of the international students constituent of our investigation sample (N=250), coming from twenty European countries all of them participant in the Bologna Process, towards a continuous and progressive development of the Intercultural Competence as a constituent element of the academic and professional profiles desirable in the Globalization Era.